Risk Factors for Stunting in Toddlers in the Public Health Center Working Area Embo Jeneponto, South Sulawesi - Rosdiana Syakur; Musaidah Musaidah Musaidah; Nur Handayani (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting is still a nutritional problem in Indonesia, including in South Sulawesi. The impact of stunting is very broad, starting from the individual, family, community, and country levels. This study aims to analyze the risk factors for stunting incidents in the Embo District Health Center Work Area, Jeneponto. The type of research used in this research is observational with a "Case-Control Study" (case-control) approach, namely the status of the research design carried out by identifying subjects in the form of cases, using primary data through interviews with questionnaires. The variables studied included maternal education, birth weight, birth length, and exclusive breastfeeding. The sampling technique uses simple random sampling. The number of samples in this study was 136 samples which included 68 case groups and 68 control groups. The results of the study showed that the variables that were risk factors for stunting were maternal education (OR= 9.758), birth weight (OR= 5.590), body length (OR= 8.065), and exclusive breastfeeding (OR= 4.286). Therefore, efforts are needed to increase the knowledge of every prospective mother by providing education on nutritional requirements for pregnant women so that they can prevent low birth weight and short birth length as well as postpartum education for exclusive breastfeeding.